A potent, broadly neutralizing human monoclonal antibody that efficiently protects hACE2-transgenic mice from infection with the Wuhan, BA.5, and XBB.1.5 SARS-CoV-2 variants - Guselnikov, Sergey V.; Baranov, Konstantin O.; Kulemzin, Sergey V.; Belovezhets, Tatyana N.; Chikaev, Anton N.; Murasheva, Svetlana V.; Volkova, Olga Y.; Mechetina, Ludmila V.; Najakshin, Alexander M.; Chikaev, Nikolai A.; Solodkov, Pavel P.; Sergeeva, Maria V.; et al. (Frontiers in Immunology, 2024)
The COVID-19 pandemic has uncovered the high genetic variability of the SARS-CoV-2 virus and its ability to evade the immune responses that were induced by earlier viral variants. Only a few monoclonal antibodies that have been reported to date are capable of neutralizing a broad spectrum of SARS-CoV-2 variants. Here, we report the isolation of a new broadly neutralizing human monoclonal antibody, iC1. The antibody was identified through sorting the SARS-CoV-1 RBD-stained individual B cells that were isolated from the blood of a vaccinated donor following a breakthrough infection. In vitro, iC1 potently neutralizes pseudoviruses expressing a wide range of SARS-CoV-2 Spike variants, including those of the XBB sublineage. In an hACE2-transgenic mouse model, iC1 provided effective protection against the Wuhan strain of the virus as well as the BA.5 and XBB.1.5 variants. Therefore, iC1 can be considered as a potential component of the broadly neutralizing antibody cocktails resisting the SARS-CoV-2 mutation escape.